(untitled) (Baghdad Science Journal, 2021)
The Atoms in Molecules (AIM) analysis for triosmium cluster, which contains trihydridede, carbon, carbonyl and 2-methylbenzothiazolide ligands, [Os3(µ-H)3(µ3-ɳ2-CC7H3(2-CH3)NS)(CO)8] is reported. Bonding features in this cluster has been analyzed based on QTAIM ("Quantum Theory of Atoms in Molecules") in this work. The topological indices derived from electron density of relevant interactions in triosmium compound have been studied. The major interesting point of the AIM analyses is that the core of part (Os3H3) reveals the absence of any critical points and bond paths connecting any pairs of Os metal atoms. However, bond critical points with their bond paths occurring between all Os-H interactions were observed. For the bridged core part (Os3H3), a 6c–6e multicenter interaction is proposed. The topological parameters computed for the bridging 2-methylbenzothiazolide ligand interactions indicate that all of these interactions are typical related to the covalent bonds with a contribution of some double-bond character.